Spatial Generation, Degeneration, and Regeneration Aerotaxis Mechanisms Toward Bio-Integrated Design - Mathilda, Gita Rahma; Andikabina, Ariko; Suryantini, Rini; Atmodiwirjo, Paramita (Universitas Muhammadiyah Makassar, 2025)
This study aims to explore spatial mechanism developed within bio-integrated design through exploring the complex natural processes of